Towards an ethical and legal foundation of the differentiated participation of the indigenous peoples in the State decisions - Daniel Cerqueira (Thēmis, 2015)
Within the Latin American state Constitutions, is the establishment of prior consultation for theindigenous peoples legitimate? Does it represent away of imposition of the minority rights in front ofthe majority rights? Does it implies a power of vetoover the state decisions? In this article, the author answers the aforementioned questions, as he assays an ethical and legal foundation for the establishment of the mechanism of free, prior and informed consultation, one that goes beyond its national and international recognition.